Pembinaan Dan Pengembangan Sumber Daya Manusia Di Sdn Sukorejo 01, Kecamatan Sukowono, Kabupaten Jember - Wachid, Mohammad Akbar Nur; Amelia, Mayaza Rizqi; Faradila, Nuria; Hasanah, Ifrotul; Hidayat, Rofiq (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Human resource development and coaching is a training devoted toeducators and education personnel in schools. This is done for the needs of theinstitution, group or individual itself. This research aims to find out how thedevelopment and coaching of human resources at SDN Sukorejo 01. The methodused in this research is atype of qualitative research involving direct observationand interviews with principals and teachers. Based on the data obtained, it showsthat the development and coaching of human resources at the school is carried outthrough several efforts, namely attending training, seminars and socialization.However, there are several obstacles faced by this school, one of which is that theindependent curriculum makes students have many activities so that teachers donot have time to attend training because they participate and help students incarrying out activities in the independent curriculum and lack of understanding ofcurrent digital technology. The results of this study are expected to contribute andillustrate the practice of coaching and developing the resources of educators andeducation personnel, especially in the Jember area.